Perbandingan Subjective Well-Being Musisi dan Non-Musisi - Christ Billy Aryanto; Stevanus Stanislaus Budi Hartono (Jurnal Ilmiah Psikologi MIND SET, 2014)
The objective of this study is to know the subjective well-being comparison between musician and non-musician. Participants of this study are musician and non-musician which is divided based on the musical activity throughout their lifespan, aged 18-40 years with the amounts of 123 participants. Musician is a person who had played a musical instrument on a regular basis for at least 10 years and joined formal musical training with the amounts of 55 participants. Non-musician is a person who had never played music, cannot read music notes, and never received formal musical training with the amounts of 68 participants. Subjective well-being was measured using the Satisfaction with Life Scale (SWLS) developed by Diener, Emmons, Larsen, and Griffin (1985) to measure cognitive evaluation and Positive Affect Negative Affect Scale (PANAS) developed by Watson, Clark, and Tellegen (1988) to measure affective evaluation. The result showed that musicians have a higher level of subjective well-being significantly than non-musicians.